Artista-professor de dança: história e formação entrecruzadas - FERREIRA, Jean Claudio Gama (2018)
In this study, biographical and descriptive, I am to investigate, analyze, and propose reflections on the formative processes of the artist-teacher. For this, I have chosen some researchers authors of the dance area to inquire about this, among them Isabel Marques, Marcia Strazzacappa, Cassia Navas and Ana Terra to make comments and reflections on the teaching artist. The methodological procedures of this research uses the biographical method, which is descriptive and qualitative and permeates the educational biography. This method comprises research and formation, by which the researcher seeks to reflect on their own formation process, and become aware of strategies, spaces and moments that, for him, had importance like formation elements throughout his life. The recollections of life experiences and teaching-learning processes in the artist and teacher formation serve data to be analyzed and observed in search for similarities and / or differences in both formations. Thus, I try to answer some questions such as, how and where is the formation of the dance artist? How teacher dance is formed? In order to trace possible analogies about the artistic practices and pedagogical processes, I present as theoretical basis Phenomenology of Perception from Maurice Merleau-Ponty. During the investigative process, assumptions and philosophical and pedagogical references, that dialogue with the issue in different ways, happen at different instances and with political-pedagogical course plans, and objectives which differ and offer specific curricular designs. Identify and build relationships between experience, research, memory, art and creation, which can supply and contribute to the construction of the artistic and academic knowledge, reflecting through textual narrative about the importance of the formation processes of the artist / teacher of dance.